Consensus-based coordination of electric vehicle charging considering transformer hierarchy. (November 2018) - Zou, Suli; Hiskens, Ian; Ma, Zhongjing
Abstract: The paper considers the coordination of electric vehicle (EV) charging where the loading on the transformers that serve the distribution feeders is taken into account. A decentralized control method is designed such that self-interested EVs are motivated to achieve global benefits. The formulation has a hierarchical structure. At the lower level, each transformer broadcasts a price signal to the EVs that it supplies, and the EVs individually determine their optimal charging strategies. At the upper level, the communication network between transformers is described as a graph and a consensus algorithm among the transformers is used to obtain a group consensus price that reflects the system generation cost. Each transformer then establishes a price which is composed of the consensus price together with a contribution that accounts for its loading characteristic. An update algorithm is developed which converges in a few (typically around ten) iterations to the unique and efficient (socially optimal) solution. Highlights: A decentralized control strategy is developed for coordinating the charging of electric vehicles. The decentralized strategy converges in a few iterations to the unique and efficient (socially optimal) solution. The control strategy has a hierarchical structure that takes into account transformer losses and capacity limits.